Antara Iman dan Transaksi: Peran Mediasi Religiusitas dalam Keputusan Pembelian Anggota BKMT Provinsi Sulawesi Selatan. - Yuliana Asnawati; Ibnu Hajar; Izza Nur Aulia; Saldi Saldi (Institut Agama Islam Negeri Palopo, 2024)
This study aims to determine the influence of halal labels on the purchase decision of cosmetic products mediated by the religiosity of the empirical evidence of BKMT South Sulawesi. The type of research used was quantitative to collect data from Muslim entrepreneurs with a questionnaire and analyzed using the Partial Least Square-Structural Equation Modelin. The findings of this study are that there is a significant relationship between the influence of halal labels on purchase decisions, halal labels on and regiliusity and there is a significant influence of religiosity on purchase decisions. This research can also provide deeper insights into the preferences of consumers who pay attention to the halal aspects of the products they buy